1997
DOI: 10.1038/sj.cdd.4400224
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and extensive lethal action of clofibrate on hepatoma cells in vitro

Abstract: Clofibrate, for a long time in use as a hypolipidemic drug, is a well known peroxisomal proliferator (PP) and hepatocarcinogen in rodents. We show here that in vitro 1 mM clofibrate induces a rapid and massive death of rat AH-130 hepatoma cells. Cell death was prominent already after 4 h of treatment, with a characteristic`apoptotic' pattern by conventional microscopy. This was further supported by the pronounced chromatin condensation detectable on 4',6-diamine-2'-phenylindole dihydrochloride (DAPI) staining,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…As well as other PPs, fibrate derivatives, among which clofibrate, were largely studied as hepatocarcinogens in rodents, also with reference to their antiapoptotic action. In this regard, however, several studies reported that clofibrate treatment induces massive apoptotic death in hepatoma cells [3,4]. In different cell lines similar observation were also reported for other PPs such as nafenopin, perfluorooctanoic acid, and BR931 [3,5,6].…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…As well as other PPs, fibrate derivatives, among which clofibrate, were largely studied as hepatocarcinogens in rodents, also with reference to their antiapoptotic action. In this regard, however, several studies reported that clofibrate treatment induces massive apoptotic death in hepatoma cells [3,4]. In different cell lines similar observation were also reported for other PPs such as nafenopin, perfluorooctanoic acid, and BR931 [3,5,6].…”
Section: Introductionmentioning
confidence: 70%
“…Such observations have been extended also to other PPs: nafenopin is able to induce apoptotic death in the AH-130 cells [3], while perfluorooctanoic acid and BR931 exert cytotoxic effects on the HepG2 hepatoma cell line [5,6]. A recent study shows that in clofibrate-treated pigs the expression of the pro-apoptotic protein Bax is up-regulated, while the levels of the antiapoptotic factor Bcl-x L are reduced, which may provide the basis for an increase of apoptotic cell death.…”
Section: Pp Cytotoxicity: Relevance To Cancer Progressionmentioning
confidence: 89%
See 3 more Smart Citations